2022
DOI: 10.1080/21505594.2022.2127209
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular bacteriolysis contributes to pathogenicity of Staphylococcus aureus by exacerbating AIM2-mediated inflammation and necroptosis

Abstract: Staphylococcus aureus can survive within phagocytes. Indeed, we confirm in this study that approximately 10% of population persists in macrophages during S. aureus infection, while the rest are eliminated due to bacteriolysis, which is of particular interest to us. Herein, we observe that the bacteriolysis is an early event accompanied by macrophage death during S. aureus infection. Furthermore, the cell death is significantly accelerated following incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…challenged the classical model stating that cell death accompanying inflammasome activation should always be pyroptosis. They demonstrated that the bacteriolysis of Staphylococcus aureus USA300 strain in infected macrophages induces AIM2-mediated necroptosis ( 117 ).…”
Section: Cross-interactions Among Pyroptosis Necroptosis and Ferropto...mentioning
confidence: 99%
“…challenged the classical model stating that cell death accompanying inflammasome activation should always be pyroptosis. They demonstrated that the bacteriolysis of Staphylococcus aureus USA300 strain in infected macrophages induces AIM2-mediated necroptosis ( 117 ).…”
Section: Cross-interactions Among Pyroptosis Necroptosis and Ferropto...mentioning
confidence: 99%
“…After S. aureus is phagocytosed by macrophages, approximately 10% of the S. aureus population will persist in macrophages, with the remaining bacteria eliminated by bacteriolysis. However, excessive bacteriolysis can cause cell death ( 67 ). Further studies confirmed that this type of cell death is not apoptosis or pyroptosis (It is characterized by dependence on inflammatory caspase enzymes, mainly caspase-1, 4, 5, 11, accompanied by the release of a large number of pro-inflammatory cytokines) but rather AIM2-mediated necroptosis ( 67 ).…”
Section: The Role Of Necroptosis In Bacterial Infectionmentioning
confidence: 99%
“…However, excessive bacteriolysis can cause cell death ( 67 ). Further studies confirmed that this type of cell death is not apoptosis or pyroptosis (It is characterized by dependence on inflammatory caspase enzymes, mainly caspase-1, 4, 5, 11, accompanied by the release of a large number of pro-inflammatory cytokines) but rather AIM2-mediated necroptosis ( 67 ). Apoptosis is known to be important for clearing pathogens ( 68 ), and the authors propose a potential immune manipulation strategy by which S. aureus sacrifices the minority to trigger a limited necroptosis, thereby releasing signals from dead cells to inhibit apoptosis and other anti-inflammatory cascades of live cells, eventually surviving within host cells and establishing infection ( 67 ).…”
Section: The Role Of Necroptosis In Bacterial Infectionmentioning
confidence: 99%
“…The CARD domain of ASC subsequently recruits procaspase-1 to the complex allowing for autocleavage of caspase-1, processing of pro-IL-1β, pro-IL18 and gasdermin D, resulting in cytokine secretion and pyroptosis. Gram-positive bacteria, including but not limited to Staphylococcus aureus and Listeria monocytogenes release dsDNA in the cytosol after escaping the phagolysosome that activates the AIM2 inflammasome ( 64 , 65 ).…”
Section: Inflammasomesmentioning
confidence: 99%
“…Additionally, phagocytosis and bacterial degradation were related to the activation of NLRP3 inflammasomes and IL-1β secretion in response to both live S. aureus and S. aureus peptidoglycan. Interestingly, IL-1β production was mediated by the NLRP3 activation, and the secretion of IL-6, KC and CCL2 was AIM2-dependent ( 120 ). Together, the NLRP3/AIM2 inflammasomes played a critical role in S. aureus infection and could be a therapeutic target to control unwanted inflammation.…”
Section: Gram-positive Bacteria Trigger Inflammasome Activationmentioning
confidence: 99%